Mental toughness: progress and prospects - Gucciardi, Daniel (2017)
Mental toughness (MT) has become a popular area of investigation and practice within sport and exercise psychology over the past two decades. Since the turn of the twenty first century, there have been hundreds of studies published on mental toughness, yet concerns remain about the conceptualisation and measurement of mental toughness. In this paper, I take stock of past work with the goal of clarifying and elaborating the most fundamental and common aspects of MT. I also look to the future and outline key substantive and methodological issues that may offer the greatest potential for refining the conceptualisation of MT and contributing to theory building on this concept. My hope is that this information will provide a platform from which to foster coherent and systematic scholarly work on MT.